Silica Gel-mediated Oxidation of Prenyl Motifs Generates Natural Product-Like Artifacts - Tang, Yu; Friesen, J. Brent; Nikolić, Dejan S.; Lankin, David C.; McAlpine, James B.; Chen, Shao-Nong; Pauli, Guido F. (Planta Medica, 2021)
Prenyl moieties are commonly encountered in the natural products of terpenoid and mixed biosynthetic origin. The reactivity of unsaturated prenyl motifs is less recognized and shown here to affect the acyclic Rhodiola rosea monoterpene glycoside, kenposide A (8), which oxidizes readily on silica gel when exposed to air. The major degradation product mediated under these conditions was a new aldehyde, 9. Exhibiting a shortened carbon skeleton formed through the breakdown of the terminal isopropenyl group, 9 is prone to acetalization in protic solvents. Further investigation of minor degradation products of both 8 and 8-prenylapigenin (8-PA, 12), a flavonoid with an ortho-prenyl substituent, revealed that the aldehyde formation was likely realized through epoxidation and subsequent cleavage at the prenyl olefinic bond. Employment of 1H NMR full spin analysis (HiFSA) achieved the assignment of all chemical shifts and coupling constants of the investigated terpenoids and facilitated the structural validation of the degradation product, 9. This study indicates that prenylated compounds are generally susceptible to oxidative degradation, particularly in the presence of catalytic mediators, but also under physiological conditions. Such oxidative artifact/metabolite formation leads to a series of compounds with prenyl-derived (cyclic) partial structures that are analogous to species formed during Phase I metabolism in vivo. Phytochemical and pharmacological studies should take precautions or at least consider the impact of (unavoidable) exposure of prenyl-containing compounds to catalytic and/or oxidative conditions.
Keywords: Rhodiola rosea; Crassulaceae; silica gel; prenyl group; oxidative degradation; artifacts